2016
DOI: 10.1177/0954405415611364
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between efficiency grouping and efficacy grouping in cell formation using the firefly metaheuristic algorithm

Abstract: Industrial environments can use several layout setups according to their convenience based on item diversity, ways of production and market demand. This work focuses on design of manufacturing cell formation. A well-known type of production layout in industrial engineering that allows meeting a diversity of production requirements and operational flexibility is the cellular manufacturing. Among the various techniques and approaches applied to manufacturing cell formation, this article uses the firefly metaheur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…8 The majority of the studies conducted on the CM design have only focused on one of these decisions; examples of studies in this relation can be found. 917 However, it should be noted that these decisions are highly inter-dependent. For example, the parameters of the FL and scheduling problems such as the material flow between machines and processing times are highly affected by the CF decision, or the transfer time between machines is directly proportional to the distance between machines.…”
Section: Introductionmentioning
confidence: 99%
“…8 The majority of the studies conducted on the CM design have only focused on one of these decisions; examples of studies in this relation can be found. 917 However, it should be noted that these decisions are highly inter-dependent. For example, the parameters of the FL and scheduling problems such as the material flow between machines and processing times are highly affected by the CF decision, or the transfer time between machines is directly proportional to the distance between machines.…”
Section: Introductionmentioning
confidence: 99%
“…6 A comparison has been made between the efficiency and efficacy (clustering) parameters of the CF solution obtained through firefly meta-heuristic algorithm applied on several benchmarked problems. 18 It has been reported, out of the comparative analysis, that the application of efficacy parameter is desirable if the reliance is on clustering, although the application of efficiency parameter can also lead to beneficial and economical layouts at the cost of inadvertence of cell clustering.…”
Section: Introductionmentioning
confidence: 99%